Electrically-driven single-photon sources based on colloidal quantum dots with near-optimal antibunching at room temperature. Issue 1 (December 2017) - Lin, Xing; Dai, Xingliang; Pu, Chaodan; Deng, Yunzhou; Niu, Yuan; Tong, Limin; Fang, Wei; Jin, Yizheng; Peng, Xiaogang
Abstract Photonic quantum information requires high-purity, easily accessible, and scalable single-photon sources. Here, we report an electrically driven single-photon source based on colloidal quantum dots. Our solution-processed devices consist of isolated CdSe/CdS core/shell quantum dots sparsely buried in an insulating layer that is sandwiched between electron-transport and hole-transport layers. The devices generate single photons with near-optimal antibunching at room temperature, i.e., with a second-order temporal correlation function at zero delay (g (2) (0)) being <0.05 for the best devices without any spectral filtering or background correction. The optimalg (2) (0) from single-dot electroluminescence breaks the lowerg (2) (0) limit of the corresponding single-dot photoluminescence. Such highly suppressed multi-photon-emission probability is attributed to both novel device design and carrier injection/recombination dynamics. The device structure prevents background electroluminescence while offering efficient single-dot electroluminescence. A quantitative model is developed to illustrate the carrier injection/recombination dynamics of single-dot electroluminescence. Single-photon sources are one of the most basic devices for quantum optical experiments and applications. Here, Lin et al. present an electrically driven single-photon source based on solution-processed colloidal quantum dots with near-optimal antibunching at room temperature.